2010
DOI: 10.1002/eat.20775
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute hepatic dysfunction in severe anorexia nervosa

Abstract: Anorexia nervosa (AN) is an eating disorder predominantly affecting young women. Abnormal liver function tests (LFT's) resulting from AN is well-described but to date few cases of dramatic rises in liver enzymes have been described. We report a 32-year-old women with severe anorexia having dramatic rise in LFT's with liver failure during extremely poor nutritional status. Acute rise in liver enzymes observed on several occasions in this patient resulted from ischaemic hepatitis secondary to liver hypoperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 12 publications
3
39
1
4
Order By: Relevance
“…23 Hepatocytes from one-quarter of patients with AN who had acute liver injury demonstrated autophagosomes, a morphologic hallmark of autophagy. 23 These findings are consistent with other studies in which authors have found resolution of liver enzyme abnormalities with nutritional support and hydration, 5,6,10,11,24,25 supporting malnutrition as a potential cause of elevated liver enzymes. Only 4.1% of patients developed elevated liver enzymes after admission compared with the larger 37.0% who presented with elevated liver enzymes on admission.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…23 Hepatocytes from one-quarter of patients with AN who had acute liver injury demonstrated autophagosomes, a morphologic hallmark of autophagy. 23 These findings are consistent with other studies in which authors have found resolution of liver enzyme abnormalities with nutritional support and hydration, 5,6,10,11,24,25 supporting malnutrition as a potential cause of elevated liver enzymes. Only 4.1% of patients developed elevated liver enzymes after admission compared with the larger 37.0% who presented with elevated liver enzymes on admission.…”
Section: Discussionsupporting
confidence: 93%
“…4 Liver enzyme abnormalities among patients with AN remain poorly characterized. The few studies of elevations in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in AN are limited to case reports [4][5][6][7][8][9][10] and studies with small sample sizes, [11][12][13][14][15] with a wide range in the reported prevalence of elevated ALT/AST, from 0% to 76%. 11 In initial studies researchers found that elevated ALT/AST was associated with lower body mass index (BMI) 11,13 and decreased percentage body fat.…”
mentioning
confidence: 96%
“…It has been suggested that recurrence of hepatic abnormalities in some patients may in some cases be related to liver hypoperfusion. 23 We studied a large cohort of 126 consecutive severely malnourished patients, hospitalized for the first time for nutritional management. This took place initially as exclusive continuous enteral nutrition (isotonic and iso-caloric) at 10 kcal/kg/d, as recommended in the literature in severe malnourished AN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have presented the relationship between low body mass index (BMI) and hepatocellular injuries [7–11]. Suggested etiologies include acute liver hypoperfusion [12, 13], hepatic steatosis with oxidative stress [6], and starvation-induced hepatocyte autophagy [14, 15]. …”
Section: Introductionmentioning
confidence: 99%